Who gets a seat at the table? The role of director characteristics in Philippine board committee membership - Lizares, Regina M. (Philippine Management Review; Vol 32 No 1 (2025): Philippine Management Review, 2025)
This study investigates the influence of directors’ characteristics on committee membership in Philippine publicly listed corporations (PLCs). This study analyzes a sample of 2,573 directors from 282 active PLCs as of the end of 2023. The findings reveal that director independence and committee linkage are significant predictors of committee membership. Committee membership patterns vary based on the committee’s role and regulatory recommendations. The audit, corporate governance, risk, and related party transaction committees, as recommended by the Philippines Code of Corporate Governance for PLC, prioritize non-executive directors with shorter tenure. In contrast, compensation, nomination, and executive committees favor longer tenured executive directors. A novel finding is the curvilinear relationship between committee linkage and committee membership, suggesting that moderate levels of committee involvement are optimal. This study enhances the understanding of factors shaping committee membership in Philippine PLCs, offering valuable insights for policymakers, boards, and investors.